2017
DOI: 10.1080/19466315.2016.1174147
|View full text |Cite
|
Sign up to set email alerts
|

Single-Arm Phase II Survival Trial Design Under the Proportional Hazards Model

Abstract: For designing single-arm phase II trials with time-to-event endpoints, a sample size formula is derived for the modified one-sample log-rank test under the proportional hazards model. The derived formula enables new methods for designing trials that allow a flexible choice of the underlying survival distribution. Simulation results showed that the proposed formula provides an accurate estimation of sample size. The sample size calculation has been implemented in an R function for the purpose of trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…To derive the sample size for the SSD, we assume that a proportional hazard (PH) model Sg(t)=false[S0(t)false]δg$S_g(t)=[S_{0}(t)]^{\delta _g}$ is satisfied for each treatment arm g=A,B$g=A, B$, where δg$\delta _g$ is the hazard ratio of treatment arm g versus the historical control arm. Under the local alternative hypothesis, it has been shown that the OSLRT Zg=(EgOg)/Eg$Z_{g}=(E_g-O_g)/\sqrt {E_g}$ is asymptotically normally distributed with mean μg=nplogδg$\mu _g=-\sqrt {np}\log \delta _g$ and unit variance, where n is the sample size per arm and p is the failure probability under the null hypothesis (Wu, 2017). Under the PH model, the hazard ratio δg$\delta _g$ can be estimated as follows (Wu, 2022): δ̂gbadbreak=OgEg,ggoodbreak=A,B.\begin{equation} \hat{\delta }_g = \frac{O_g}{E_g}, \;\;\; g=A, B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To derive the sample size for the SSD, we assume that a proportional hazard (PH) model Sg(t)=false[S0(t)false]δg$S_g(t)=[S_{0}(t)]^{\delta _g}$ is satisfied for each treatment arm g=A,B$g=A, B$, where δg$\delta _g$ is the hazard ratio of treatment arm g versus the historical control arm. Under the local alternative hypothesis, it has been shown that the OSLRT Zg=(EgOg)/Eg$Z_{g}=(E_g-O_g)/\sqrt {E_g}$ is asymptotically normally distributed with mean μg=nplogδg$\mu _g=-\sqrt {np}\log \delta _g$ and unit variance, where n is the sample size per arm and p is the failure probability under the null hypothesis (Wu, 2017). Under the PH model, the hazard ratio δg$\delta _g$ can be estimated as follows (Wu, 2022): δ̂gbadbreak=OgEg,ggoodbreak=A,B.\begin{equation} \hat{\delta }_g = \frac{O_g}{E_g}, \;\;\; g=A, B.…”
Section: Methodsmentioning
confidence: 99%
“…To derive the sample size for the SSD, we assume that a proportional hazard (PH) model 𝑆 𝑔 (𝑡) = [𝑆 0 (𝑡)] 𝛿 𝑔 is satisfied for each treatment arm 𝑔 = 𝐴, 𝐵, where 𝛿 𝑔 is the hazard ratio of treatment arm 𝑔 versus the historical control arm. Under the local alternative hypothesis, it has been shown that the OSLRT 𝑍 𝑔 = (𝐸 𝑔 − 𝑂 𝑔 )∕ √ 𝐸 𝑔 is asymptotically normally distributed with mean 𝜇 𝑔 = − √ 𝑛𝑝 log 𝛿 𝑔 and unit variance, where 𝑛 is the sample size per arm and 𝑝 is the failure probability under the null hypothesis (Wu, 2017). Under the PH model, the hazard ratio 𝛿 𝑔 can be estimated as follows (Wu, 2022):…”
Section: Sample Size For the Two-arm Ssdmentioning
confidence: 99%
“…The OSLRT was first introduced by Breslow, and its applications to the single‐arm phase II trial designs were discussed by Sun et al, Kwak and Jung, Wu, Schmidt et al, and Belin et al The study design based on the OSLRT requires each patient to be followed until an event occurs or until the end of study. In real practice, however, the full follow‐up information for a phase II trial is often difficult to obtain in the late period of trial, particularly when the accrual duration is long; obtaining the status of each patient within a restricted period is more realistic …”
Section: One‐sample Log‐rank Testmentioning
confidence: 99%
“…Table also gives results for the comparison between proposed design to Belin's design under the exponential model. The proposed design provided an accurate power while Belin's design did not preserve power for some scenarios because Belin's design uses an approximate variance estimate that could either underestimate or overestimate the exact variance of the OSLRT …”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation